STUDI PENGARUH PERBANDINGAN REAKTAN LIGNIN NaHSO3 DAN pH TERHADAP NATRIUM LIGNOSULFONAT (NaLS) - Gustini Syahbirin; Ani Suryani; Tesar Dzikrulloh (Jurnal Riset Kimia, 2008)
ABSTRACT Lignin was isolated from waste black liquor of soda pulping process. Sulfonation of soda lignin produced Sodium Lignosulfonate (NaLS) which can be used as dispersants, and concrete admixtures. In this research, sulfonation was carried out towards lignin with ratio of lignin-NaHSO3 of 1.0:0.4; 1.0:0.5; and 1.0:0.6, and initial pH of 5.00; 6.00; 7.00. Parameters observed were purity, final pH, and yield of NaLS. The upsurge of initial pH increased the final pH and NaLS yield, but decreased its purity. The upsurge of ratio of lignin-NaHSO3 increased NaLS yield and decreased its purity, but did not affect the final pH of NaLS. The chosen optimum condition was on pH of 6.00 and ratio of lignin-NaHSO3 of 1.0:0.6. Characterization of functional group using FTIR, and purity of NaLS using UV-Visible Absorption Spectrophotometer. Keywords: soda lignin, sulfonation of lignin, sodium lignosulfonate